2022
DOI: 10.1159/000521372
|View full text |Cite
|
Sign up to set email alerts
|

Where Are We with Deep Brain Stimulation? A Review of Scientific Publications and Ongoing Research

Abstract: <b><i>Background:</i></b> Deep brain stimulation (DBS) is a neuromodulatory technique that delivers adjustable electrical stimuli to brain targets to relieve symptoms associated with dysregulated neural circuitry. Over the last several decades, DBS has been applied to a number of conditions, including motor, pain, mood, and cognitive disorders. An assessment of the body of work in this field is warranted to determine where we have been, define the current state of the field, and chart a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Following the publication in September 2001 in the New England Journal of Medicine of a worldwide multicentre trial of DBS in STN or in GPi [33], FDA approved these procedures for surgical treatment of patients with advanced PD, and they eventually received endorsement as efficient and safe by the International Parkinson and Movement Disorders Society [18]. DBS of the STN and the GPi became, since then, and still are, the most popular and world-spread methods for surgical treatment of PD [34].…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…Following the publication in September 2001 in the New England Journal of Medicine of a worldwide multicentre trial of DBS in STN or in GPi [33], FDA approved these procedures for surgical treatment of patients with advanced PD, and they eventually received endorsement as efficient and safe by the International Parkinson and Movement Disorders Society [18]. DBS of the STN and the GPi became, since then, and still are, the most popular and world-spread methods for surgical treatment of PD [34].…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…Data from the SANTE study showed a gradual improvement in neuropsychological outcome and quality of life from baseline based on the Liverpool seizure severity scale and Qualie‐31 scores 21 . Neuropsychological test composite scores showed statistically significant gains from baseline to 5 years including attention, executive function, depression, tension anxiety, total mood disturbance, and subjective cognitive function.…”
Section: Discussionmentioning
confidence: 98%
“…There is no doubt that DBS is and will remain for the foreseeable future the procedure of choice for patients with PD and other movement disorders, especially considering all the innovations and development of new hardware, new modes of stimulation, new indications, etc. [53], let alone the limitless potentials of DBS for enabling scientific discoveries and for research [54]. However, on a more down-to-earth level, Leksell-Laitinen's posteroventral pallidotomy is surviving and will remain an efficacious and needed procedure, including when DBS is not available or not affordable, or when it fails.…”
Section: Discussionmentioning
confidence: 99%